Resurrecting Gaia: harnessing the Free Energy Principle to preserve life as we know it - Montgomery, Caspar; Hipólito, Inês (Frontiers in Psychology, 2023)
This paper applies the Free Energy Principle (FEP) to propose that the lack of action in response to climate change should be considered a maladaptive symptom of human activity that we refer to as biophilia deficiency syndrome. The paper is organised into four parts: the characterisation of the natural world under the Gaia Hypothesis, the employment of the FEP as a description of the behaviour of self-organising systems, the application of the FEP to Gaia to understand coupling dynamics between living systems and purportedly non-living planetary processes, and the offering of positive interventions for addressing the current state of ecological crisis under this framework. For the latter, we emphasise the importance of perturbing stuck states for healthy development, and the necessary appreciation of life existing as nested systems at multiple levels in a hierarchy. We propose the development of human biophilia virtue in accordance with the FEP as a practical intervention for treating biophilia deficiency syndrome and helping to safeguard the balance of planetary processes and the integrity of living systems that depend on them, offering some examples of what this might look like in practice. Overall, this paper provides novel insights into how to catalyse meaningful ecological change, proposing a deliberate and disruptive approach to addressing the dysfunctional relationship between humans and the rest of the natural world.